Texture image analysis of normal appearing white matter areas in clinically isolated syndrome that evolved in demyelinating lesions in subsequent MRI scans: multiple sclerosis disease evolution - Loizou, Christos P.; Seimenis, Ioannis; Kasparis, Takis (My University, 2010)
The purpose of this paper is to explore the use of texture features analysis for evaluating normal appearing white matter (NA WM) areas in brain Magnetic Resonance Imaging (MRI) scans of patients with a first demyelinating event (Clinically Isolated Syndrome-CIS) that have been subsequently converted (in follow up MRI scans) in demyelinating plaques. Texture features analysis was carried out in NA WM areas selected from transverse sections of T2-weighted MRI scans acquired from 10 untreated subjects that had developed their first neurological-demyelinating event (CIS). All NA WM areas and demyelinating lesions were manually segmented by an experienced multiple sclerosis (MS) neurologist. The patients were twice scanned with brain MRI with an interval of6-12 months (time 0, initial MRI and time 6-12, repeated MRI scan). Areas in repeated MRI scan, where new lesions had been developed, were mapped back to their corresponding initial MRI scan NA WM areas. Following that, texture features were extracted from those NA WM areas that evolved to demyelinating lesions and compared to texture features extracted from NA WM areas of the initial MRI scan that didn't evolve to demyelinating lesions. It was shown that for the texture features investigated, no single feature could be used to differentiate between NA WM at 0 months (NAW-C-O), and ROIS that will evolve into demyalating lesions also at 0 months (ROIS-O). Several features could be used to differentiate between ROIS-O vs Lesions at months, NA WM at 6 months and Lesions at 6 months, as well as between Lesions at 0 months vs Lesions at 6 months. Future work will investigate the proposed method on more subjects.
Keywords: Information technology; Magnetic resonance imaging; Correlators; Demyelination; Neurophysiology